Estado de Exceção como realidade permanente do processo de acumulação de capital - Seracinskis Junior, Roberto Eduardo (2019)
This thesis critically discusses the idea of State of Permanent Exception developed by Giorgio Agamben in dialogue with Carl Schmitt, the main theoreticians, classical and contemporary, respectively, of the State of Exception. In his main works, Agamben recovers the practices of Nazism and considers it the paradigm of the State of Permanent Excellency, transformed into a mode of management of contemporary governments. Thus, the figure of a Führer, the Sovereign, produces the naked life of biopolitics, the homo sacer, which is configured in a life that cannot be killed, and whose death is homicide, whose concentration is the space of indistinction between the legal and Hi cool. With such characteristics, the State of Exception becomes permanent, without the need for a state of emergency to justify its establishment, as previously understood. Starting from the derivationist and materialist conceptions of the State and Law (Joachim Hirsch and Pachukanis) and the understanding of the Primitive and Permanent Capital Accumulation process (Marx, Luxemburg and Harvey) this conception is analyzed critically in order to understand that the State of Exception , although it is permanent, responds and is shaped by the needs of the Accumulation process and is regulated in the present times by the neoliberal regime. The modulation and forms assumed by the State of Exception depends on the accumulation conditions, social and historical of each country, and the relation of forces that influences and participates in the State. The neoliberal promotion of inequality, the reduction of rights, the precariousness of work, the increase of punitivism, the breakdown of solidarities and exacerbated individualism are the current consequences of this State of Exception, with the judiciary having a fundamental role in defining the Exception, under the command of the neoliberal regime, and defining the enemy of the exception as homo sacer, whose life can be killable, not only physically, but symbolically.